Pengaruh Independensi, Kompleksitas Tugas, dan Pengalaman Auditor terhadap Audit Judgment : Studi Empiris pada Kantor Akuntan Publik di Bekasi - Dina Juniarti Barokah; Istianingsih Sastrodiharjo; Aloysius Harry Mukti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to test and analyze the influence of independence, task complexity, and auditor experience on audit judgment. Audit judgment is one of the important components in the audit process that determines the quality of audit report results. The better the auditor's consideration, the higher the level of reliability of the audited financial statements. This research was conducted at Public Accounting Firms (KAP) operating in the Bekasi area. The variables used in this study consisted of audit judgment as a dependent variable, and independence, task complexity, and auditor experience as independent variables. The sampling technique was carried out using a non-probability sampling method, using a purposive sampling approach. The sample obtained was 12 companies with a total of 76 auditor respondents. The analysis method used is Structural Equation Modeling Partial Least Square (SEM-PLS) by measuring three stages: outer model test, inner model test, and hypothesis test. The results of the study show that the three independent variables, namely independence, task complexity, and auditor experience, have a positive and significant influence on audit judgment. This means that the higher the level of auditor independence, the more complex the tasks handled, and the more experience the auditor has, the better the audit considerations will be in the audit decision-making process. The implications of this study underscore the importance of maintaining and improving the quality of auditor professionalism, through continuous training, increasing flight hours, and maintaining an independent attitude in carrying out the audit process. In addition, the organization is also expected to provide adequate support for the sustainable development of auditor competencies. It is hoped that these findings can be an input for public accounting firms and related institutions in improving the quality of financial audit results and strengthening public trust in the auditor profession.